2014
DOI: 10.1002/jib.161
|View full text |Cite
|
Sign up to set email alerts
|

Protein content of grains of different size fractions in malting barley

Abstract: The negative relationship between grain size (percentage >2.5 mm) and protein content usually observed in barley grain samples is attributed to the presence of thin grains. The objective of this study was to determine whether, in grain samples from a given environment, thin grains had a different protein content than plump grains. Grain samples from field experiments were analysed for grain yield, size and protein content of the whole sample and of four size fractions within each sample. Grain yield ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 22 publications
(35 reference statements)
4
35
1
Order By: Relevance
“…Higher percentage malt nitrogen as well as protein contents observed in the sorghum malts vis-à-vis the percentage grain nitrogen and proteins are consistent with earlier reports and are attributable to carbohydrase activity during germination resulting in increased nitrogen content (Agu and Palmer, 2013). Specific protein level and high grain size are usually required by maltsters to produce good quality malt from barley grains (Magliano et al, 2014). Malting loss of SV and SSV ranged from 16.3 to 26.0% and fell within those reported for sorghum malts (Owuama and Asheno, 1994;Subramanian et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…Higher percentage malt nitrogen as well as protein contents observed in the sorghum malts vis-à-vis the percentage grain nitrogen and proteins are consistent with earlier reports and are attributable to carbohydrase activity during germination resulting in increased nitrogen content (Agu and Palmer, 2013). Specific protein level and high grain size are usually required by maltsters to produce good quality malt from barley grains (Magliano et al, 2014). Malting loss of SV and SSV ranged from 16.3 to 26.0% and fell within those reported for sorghum malts (Owuama and Asheno, 1994;Subramanian et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…1A). Although protein synthesis has been linked to drought stress tolerance owing to the activation of heat shock proteins for osmoregulation, too low protein content may impact on kernel size and malt production (Magliano et al 2014). However, when grain quality of the heat-stressed SG samples was compared against commonly grown barley cultivars, protein and starch contents were found not to be negatively correlated but independent of each other (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The protein content of the heat-stressed grain, irrespective of SG expression, was significantly (P < 0.05) higher than that of the parental lines and commonly grown cultivars (Tables I and II) and much lower than that of the water-stressed grain samples. Although protein synthesis has been linked to drought stress tolerance owing to the activation of heat shock proteins for osmoregulation, too low protein content may impact on kernel size and malt production (Magliano et al 2014). During malting, proteins are degraded into amino acids and small peptides, providing nutrients for brewer's yeasts growth, sugar metabolism, and enzyme synthesis (Jones 2005).…”
Section: Resultsmentioning
confidence: 99%
“…3), which is more representative of historical rainfall averages, could be useful to estimate the rate of N fertilization needed to obtain a given GPC, when the target yield is estimated, but if environmental conditions substantially affect the obtained yield, its predictability is reduced. Magliano et al (2014) found a lower Yintercept (7.267) and a higher slope (0.08) when relating N availability per Mg of grain yield. This was probably due to the use of Scarlett variety, which tends to have lower GPC compared to more modern varieties, and to different environmental conditions during grain fill.…”
Section: Yield Protein and Kernel Plumpness Response To N Fertilizatmentioning
confidence: 87%
“…This was probably due to an increased grain set in distal spikelets and in spikes from tillers when N was applied at tillering, increasing grain number and decreasing the source/sink relationship. In addition, smaller grains tend to have a higher GPC than larger kernels (Prystupa and Ferraris, 2011;Magliano et al, 2014). There was a slight but non-significant positive correlation (r=0.47; p<0.15) between KP and grain yield in the control treatments (data not shown), suggesting that kernel size was a significant component of yield only in some site-years.…”
Section: Yield Protein and Kernel Plumpness Response To N Fertilizatmentioning
confidence: 96%